Working from home and public transit use in Canada, 2016 to 2023 - Tahsin Mehdi; René Morissette (Economic and Social Reports)
The increase in work from home triggered by the COVID-19 pandemic directly decreased public transit use. While this increase in work from home likely reduced commuting and greenhouse gas emissions caused by transportation, it also put downward pressure on the revenues and ridership of urban public transit systems. This article assesses the degree to which the increase in work from home observed in Canada in recent years may have reduced the number of public transit commuters from 2016 to 2023 in urban areas.